SP1.2.6 Expanding the General Surgery Extended Surgical Team improves service delivery and provides increased training opportunities for surgical trainees. (9th August 2022) - Luffman, William; Duff, Sarah; Capozzi, Patrizia; Sharpe, Gail; Hine, Rachael
Abstract: Aim: The Extended Surgical Team (EST) provides an additional surgical workforce with transferable skills. By expanding our EST and developing our Surgical Ambulatory Care service, we aimed to improve the delivery of acute surgical care to our patients. This also allowed us to improve CST training experience by supporting the CST on-call, providing an admissions base, helping decision making and maximising trainee educational opportunities. Method: As part of an HEE EST Project, we used funding to expand the ambulatory care unit and employ/train further surgical ACPs. We surveyed the core trainee group regarding their on-call working pattern, training opportunities when on-call and where most time was spent. We implemented a change of working to utilise the new expanded EST, reducing the CST (and patient) time in ED. We re-surveyed the group after intervention. Results: Results showed a reduction in the amount of time CSTs were spending with patients in the emergency department, easing the pressure on ED. Results showed support for the decision making on-call was greatly improved and the workload eased, allowing for improved educational opportunities for the trainee. Conclusion: We have shown that the expansion of the EST and ambulatory service, when properly utilised by the surgical team, improves the training opportunities available to junior trainees, whilst also improving the delivery of General Surgery acute services by reducing the surgical patient pressure on our already stretched emergency department. We plan to continue the expansion of our EST and new model of delivery of CST on-call services.